Serious Game for rehabilitation of Hemiparetic Stroke patients: impact on quality of life (Research, Society and Development, 2022)
Hemiparesis is the typical clinical picture of stroke, resulting in important functional losses that compromise the quality of life (QOL) of patients. Although conventional physiotherapy is beneficial in rehabilitation, there are some limitations. Serious Games (SG) correspond to a viable alternative in rehabilitation because they make the process more motivating. The objective was to verify the therapeutic effects of an exercise program using a SG on the motor functions of the lower limbs, functional mobility and QOL of post-stroke hemiparetic patients. This is a non-randomized controlled clinical trial involving 24 patients in the subacute or chronic phase of the disease. The experimental group (EG n=16) received treatment for the paretic lower limb using SG mim-Pong. The control group (CG n=8) received treatment with conventional kinesiotherapy. Twenty sessions were held (twice a week), lasting 30 minutes. The following were evaluated: motor impairment (Fugl-Meyer-FMAS), cognitive level (Mini Mental State Examination), functional mobility (Timed Up and Go Test), QOL perception (Nottingham-PSN Health Profile) and perception of improvement (Likert Scale). Significant improvements were observed only in the GE. We highlight the large effect size (ES) obtained in the variables evaluated with the PSN (ES=0.5) and the FMAS (ES=0.6). There was also superiority of the GE in the perception of improvement. It is concluded that the SG mim-Pong can be considered as a valuable resource in the rehabilitation of hemiparetic stroke patients, as it provided motor and functional improvements, which directly impacted on the quality of life, and these improvements were superior to those obtained with conventional physiotherapy.